Um estudo sobre a autonomia financeira dos municípios paraibanos - Silva Néto, Arnaldo Oliveira da (2022)
An effective public revenue sharing system is essential to guarantee the financial autonomy of federal entities, considering the theoretical bases of Fiscal Federalism. However, the formation of the Brazilian Federation was marked by coronelismo and clientelism, phenomena harmful to the guarantee of autonomy of local federated entities. In the same sense, the diversity existing among the Municipalities of the State of Paraíba, in demographic and economic terms, can influence the way in which these entities obtain their public revenues, being more or less dependent on the transferred revenues. Based on these considerations, this research aimed to analyze and answer the following question: what is the behavior of the financial autonomy of municipalities in Paraíba, considering their demographic and economic profiles? Following these two criteria, the Municipalities were subdivided into five groups, and went through a methodological process so that five Municipalities were selected in each group, making this research executable. The time lapse researched consisted of the financial years from 2016 to 2019. Regarding the methodology, the deductive method was adopted, in the research approach, regarding the objectives, it is characterized as descriptive, regarding the nature, it is classified as applied, regarding the procedures, it can be classified as historical, bibliographical, documentary and ex-post fact, finally, regarding the approach to the problem, it‘s considered a qualitative research. The results obtained corresponded to the two initial assumptions developed, indicating a tendency for the less populous and poorer Municipalities to be less financially autonomous than the more populous and rich ones. Finally, it was concluded that the Brazilian federative model doesn‘t favor the financial autonomy of less favored municipalities, making them overly dependent on intergovernmental transfers from the Union and the State.